Analisis Kinerja Badan Pertanahan Nasional Dalam Pelayanan Sertifikasi Tanah (Studi pada Badan Pertanahan Nasional Kota Malang) - Fenny Ardila Witriany (Jurnal Administrasi Publik, 2016)
Abstract: Performance Analysis of National Land Agency in The Service of Certification of Land (Study on National Land Agency of Malang). Since the order of the reform , the government is committed to improving its performance . Various regulations published as efforts to improve the public service sector . But in fact almost all sectors , including land , bureaucratic public services are still not satisfactory. It takes commitment to improve their performance. Through indicators of productivity , responsiveness , accountability and service quality can be measured quality of the performance of public services. The results show , the performance of BPN Malang is sufficient when the review of indicators of productivity , responsiveness and quality of service. But accountability is not sufficient about the standard operating procedures of service . Need to simplification of procedures for all of its services , as well as an increase in complaints management system given the potential problems of increasingly complex land .. Keywords: service performance, bureaucratic land Abstrak: Analisis Kinerja Badan Pertanahan Nasional Dalam Pelayanan Sertifikasi Tanah (Studi Pada Badan Pertanahan Nasional Kota Malang). Sejak orde reformasi, pemerintah bertekad memperbaiki kinerjanya. Beragam regulasi diterbitkan sebagai upaya perbaikan sektor pelayanan publik. Namun ternyata hampir di semua sektor, termasuk pertanahan, birokrasi pelayanan publik masih belum memuaskan. Dibutuhkan komitmen aparatur penyelenggara pelayanan publik untuk meningkatkan kinerjanya. Melalui indikator produktivitas, responsivitas, akuntabilitas, dan kualitas layanan bisa diukur kualitas kinerja pelayanan publik tersebut. Hasil penelitian menunjukkan, kinerja BPN Kota Malang cukup memadai bila ditinjau dari indikator produktivitas, responsivitas dan kualitas layanannya. Namun akuntabilitas belum cukup memadai utamanya menyangkut standar operasi prosedur layanan. Perlu penyederhanaan prosedur semua jenis pelayanan, serta peningkatan sistem pengelolaan pengaduan mengingat potensi permasalahan pertanahan semakin kompleks. Kata kunci: kinerja pelayanan, birokrasi pertanahan